The effect of Abi3 locus deletion on the progression of Alzheimer’s disease-related pathologies - Karahan, Hande; Smith, Daniel C.; Kim, Byungwook; McCord, Brianne; Mantor, Jordan; John, Sutha K.; Al-Amin, Md Mamun; Dabin, Luke C.; Kim, Jungsu (Frontiers in Immunology, 2023)
Human genetics studies of Alzheimer’s disease (AD) have identified the ABI3 gene as a candidate risk gene for AD. Because ABI3 is highly expressed in microglia, the brain’s immune cells, it was suggested that ABI3 may impact AD pathogenesis by regulating the immune response. Recent studies suggest that microglia have multifaceted roles in AD. Their immune response and phagocytosis functions can have beneficial effects in the early stages of AD by clearing up amyloid-beta (Aβ) plaques. However, they can be harmful at later stages due to their continuous inflammatory response. Therefore, it is important to understand the role of genes in microglia functions and their impact on AD pathologies along the progression of the disease. To determine the role of ABI3 at the early stage of amyloid pathology, we crossed Abi3 knock-out mice with the 5XFAD Aβ-amyloidosis mouse model and aged them until 4.5 months old. Here, we demonstrate that deletion of the Abi3 locus increased Aβ plaque deposition while there was no significant change in microgliosis and astrogliosis. Transcriptomic analysis indicates alterations in the expression of immune genes, such as Tyrobp, Fcer1g, and C1qa. In addition to the transcriptomic changes, we found elevated cytokine protein levels in Abi3 knock-out mouse brains, strengthening the role of ABI3 in neuroinflammation. These findings suggest that loss of ABI3 function may exacerbate AD progression by increasing Aβ accumulation and inflammation starting from earlier stages of the pathology.